Hedonism in William Shakespeare’s Drama “Antony and Cleopatra” - Nurdelia Nasution; Salsah Br. Nainggolan; Reva Angelina; Annisa Ananda Utomo; Syamsul Bahri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
William Shakespeare’s drama Antony and Cleopatra illustrates various aspects of hedonism, especially in the pursuit of love, power, and desire. These behaviors are reflected in the way the characters prioritize personal pleasure over political duty, showing how immediate gratification often clashes with responsibility. This study aims to explore the different types of hedonism represented in the play. A qualitative descriptive approach is used to analyze the dialogues and actions of the main characters, Mark Antony and Cleopatra, based on Weijers’ (2012) framework. The results reveal six categories of hedonism: folk hedonism (30%), value/prudential hedonism (20%), motivational hedonism (15%), normative hedonism (12.5%), utilitarian hedonism (12.5%), and egoist hedonism (10%). Among these, folk hedonism is the most dominant, particularly in Antony and Cleopatra’s pursuit of love and passion without considering the consequences for their political roles. The research shows that Antony and Cleopatra reflects how the pursuit of personal pleasure can shape character development, create conflict, and even lead to tragedy, illustrating timeless patterns where short-term desires overshadow long-term responsibilities.